Retrospective Study of Clinical Cases in Ruminants at the UFRGS Veterinary Teaching Hospital - Borowsky, Aline Moreira; de Castro Beck, Carlos Afonso; Oberst, Eneder Rosana; Correa Rivero, Beatriz Riet; Melo, Luciano Cavalheiro; Bueno, Flávia Umpierre; Loss, Daiane Elisa; Raimondo, Raquel Fraga e Silva (Acta Scientiae Veterinariae, 2019)
Background: The pillars of animal production are sanity, genetics and nutrition. Sanitary control of the herd is important to reduce production costs and maintain health. The Veterinary Clinics Hospital (HCV) of the Federal University of Rio Grande do Sul (UFRGS), located in Porto Alegre - RS, is the place of greatest casuistry of the state, with 20.000 annual attendances, between small and large animals. In view of this scenario, the present study aimed to determine the frequency and characterize the ruminants attended at HCV, in order to help in the future, in the construction of control and prevention strategies of diseases found. Materials, Methods & Results: The documents of ruminant care between January 2007 and May 2018 were searched in the archives of the Hospital of Veterinary Clinics of UFRGS. Data on species, race, sex, age and diagnosis were collected. Diagnoses were classified as conclusive and inconclusive and the cases with conclusive diagnosis were classified according to etiology: infectious and parasitic diseases, metabolic and nutritional diseases, reproductive and obstetric diseases, toxic diseases, traumatic diseases. The prevalence of diseases and characteristics of ruminants attended (species, sex, category) was calculated. During the study period, between January 2007 and May 2018, 341 ruminants were attended, with emphasis on sheep (42%), goats (39%) and cattle (18%). In addition, a camel with foreign body obstruction, a sambar deer with fracture of the first thoracic vertebra and a buffalo with ruminal impaction were attended. The care profile was mapped, with predominance of females (57%) and adults (59%). Most of the animals did not present a defined breed, but among the breeds stands out Texel, of cutting aptitude, in sheeps and Saanen and Holstein, of dairy aptitude, in goats and cattle, respectively. In the retrospective study, the diseases with infectious and parasitic etiology presented the highest prevalence with 27.5% of the attendances, followed by reproductive (17.5%), traumatic (13.5%), metabolic (10%), others (10%) and toxic (2.5%). Sixty-six animals had inconclusive diagnosis (19.5%). Discussion: The highest prevalences were infectious and parasitic diseases, with emphasis on myiasis and verminosis. So, it is perceived that management corrections are sufficient to reduce the number of occurrences of diseases and prophylactic measures such as vaccination protocol, vermifugation and adequate nutritional management are allied in this walk. Among the reproductive diseases, dystocia (42.85%), which is one of the main causes of mortality in the peripartum period, has been highlighted. Dog attack was the major cause of traumas in ruminants and urolithiasis was highlighted in metabolic diseases. In toxic diseases, copper intoxication was the most important. Sheep are extremely sensitive to this intoxication, as they tend to accumulate copper in the organism. The retrospective study made it possible to visualize the panorama of HCV UFRGS visits to ruminants in the last years, mapping the profile and determining the casuistry of the diseases. Studies of hospital veterinary casuistry are rare, mainly involving ruminants. At the end, it is concluded that studies referring to casuistry are important to know the predominant diseases in a specific area and its risk factors considering differential diagnosis and future prevention programs.